Liquid Chromatography Coupled to High-Resolution Mass Spectrometry for the Confirmation of Caribbean Ciguatoxin-1 as the Main Toxin Responsible for Ciguatera Poisoning Caused by Fish from European Atlantic Coasts - Pablo Estevez; Manoella Sibat; José Manuel Leão-Martins; Pedro Reis Costa; Ana Gago-Martínez; Philipp Hess (Toxins, 2020)
Ciguatera poisoning (CP) is a common seafood intoxication mainly caused by the consumption of fish contaminated by ciguatoxins. Recent studies showed that Caribbean ciguatoxin-1 (C-CTX1) is the main toxin causing CP through fish caught in the Northeast Atlantic, e.g., Canary Islands (Spain) and Madeira (Portugal). The use of liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) combined with neuroblastoma cell assay (N2a) allowed the initial confirmation of the presence of C-CTX1 in contaminated fish samples from the abovementioned areas, nevertheless the lack of commercially available reference materials for these particular ciguatoxin (CTX) analogues has been a major limitation to progress research. The EuroCigua project allowed the preparation of C-CTX1 laboratory reference material (LRM) from fish species (Seriola fasciata) from the Madeira archipelago (Portugal). This reference material was used to implement a liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) for the detection of C-CTX1, acquisition of full-scan as well as collision-induced mass spectra of this particular analogue. Fragmentation pathways were proposed based on fragments obtained. The optimized LC-HRMS method was then applied to confirm C-CTX1 in fish (Bodianus scrofa) caught in the Selvagens Islands (Portugal).